The PRIDIKSI DEBIT PUNCAK SUNGAI AIR KETAHUN HULU KABUPATEN LEBONG DENGAN MENGGUNAKAN METODE HIDROGRAF SATUAN SINTETIK GAMA I - Haris Ifawan Zega; Khairul Amri; Muhammad Fauzi (Jurusan Teknik Sipil Universitas Bangka Belitung, 2021)
ABSTRACT The Ketahun Downstream watershed (DAS) is one of the watersheds in Lebong. The Air Ketahun Downstream River Basin flows from the upstream area located in the Lebong Regency. The purpose of this study was to obtain the planned peak discharge on Talang Bunut Village and its surroundings due to frequent flooding when the water discharge rises in the Air Ketahun Down Stream Basin in analyzing hydrology using HSS Gama 1. Rainfall is very influential on the amount of water flowing in a river. Hydrological analysis to obtain peak discharge in this way uses daily rainfall data for 10 years. The peak discharge obtained in the Air Ketahun Downstream watershed in Talang Bunut village, Uram Jaya sub-district, Lebong Regency for a 100-year return period using the HSS Gama I method, which is 3030.45 m3 / second with a peak time of 2. Keywords: Rainfall, Synthetic unit hydrograph, Peak discharge.